Sistem Pakar Mendiagnosa Penyakit Ayam Kampung Menggunakan Metode Certainty Factor - Sri Wahyuni; Paska Marto Hasugian (CV. Utility Project Solution, 2022)
Animal husbandry is the activity of breeding and raising livestock to obtain the benefits and results of these activities. Activities in the field of animal husbandry can be divided into two groups, namely livestock farming of large animals such as cows, buffaloes and horses, while the second group is farming of small animals such as chickens, ducks, birds and others. Village chicken farming activities have existed since ancient times. Village chickens start from the first generation, namely from the descendants of the red jungle fowl (Gallus gallus). Raising free-range chickens is not easy because there are many things that must be considered and must have problems, therefore an expert system is needed to assist farmers in diagnosing and knowing the type of disease and symptoms experienced by the free-range chicken using a computer system automatically. This expert system uses the Certainty Factor method which aims to measure the level of certainty of facts or rules to describe an expert's belief in the problem at hand. This study shows how the process of calculating the Certainty Factor method in diagnosing free-range chicken disease with the initial combination rule to the last combination rule based on the selected symptoms, it can be concluded that the highest weight value is D01 Avian Influenza with a weight value of 0.99 x 100% = 99%